PENGARUH TINGKAT SUKU BUNGA, NILAI TUKAR DAN INFLASI TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - Sibarani, Catherine Putri; Napitupulu, Elkezia Nopita Dina; Sembiring, Jessi Charina; Lenas, Meldilianus N. J. (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the effect of interest rates, exchange rates, and inflation on firm value, with profitability as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange in 2020-2024. The sample size was 14 property and real estate companies. The sampling technique used was the purposive sampling method, with 14 companies as the sample with 70 observations. The analytical method used was MRA (Moderated Regression Analysis) using SPSS analysis tools. The results showed that partially, interest rates did not significantly affect firm value, while exchange rates significantly affected firm value. Inflation also significantly affected firm value. Furthermore, the results of the moderation test showed that profitability was unable to moderate the effect of interest rates on firm value. Profitability was unable to significantly moderate the effect of exchange rates on firm value, but showed a positive relationship. In addition, profitability was also unable to moderate the effect of inflation on firm value.